2011
DOI: 10.1128/aem.00234-11
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Response of the Amoeba Acanthamoeba castellanii to Chlorine, Chlorine Dioxide, and Monochloramine Treatments

Abstract: Acanthamoeba castellanii is a free-living amoebae commonly found in water systems. Free-living amoebae might be pathogenic but are also known to bear phagocytosis-resistant bacteria, protecting these bacteria from water treatments. The mode of action of these treatments is poorly understood, particularly on amoebae. It is important to examine the action of these treatments on amoebae in order to improve them. The cellular response to chlorine, chlorine dioxide, and monochloramine was tested on A. castellanii t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
21
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 26 publications
4
21
1
Order By: Relevance
“…Previous research has revealed that cocultures of the pathogenic Burkholderia species Burkholderia pseudomallei with the ubiquitous freshwater amoeba Acanthamoeba astronyxis greatly enhances the survival of B. pseudomallei in the presence of monochloramine, with 100 times more monochloramine required to maintain disinfectant efficacy when the amoeba was present (29). This is due to the ability of Acanthamoeba cysts to resist common disinfectants, such as monochloramine and chlorine, and their ability to bear phagocytosis-resistant bacteria within, thus protecting the bacteria from water treatments (30). While these particular species may not have been present in these systems, it may be the case that similar interkingdom interactions can occur for other Burkholderiales species.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed that cocultures of the pathogenic Burkholderia species Burkholderia pseudomallei with the ubiquitous freshwater amoeba Acanthamoeba astronyxis greatly enhances the survival of B. pseudomallei in the presence of monochloramine, with 100 times more monochloramine required to maintain disinfectant efficacy when the amoeba was present (29). This is due to the ability of Acanthamoeba cysts to resist common disinfectants, such as monochloramine and chlorine, and their ability to bear phagocytosis-resistant bacteria within, thus protecting the bacteria from water treatments (30). While these particular species may not have been present in these systems, it may be the case that similar interkingdom interactions can occur for other Burkholderiales species.…”
Section: Discussionmentioning
confidence: 99%
“…Theculturemedium was eliminated and bacteria were fixedw ith 3% glutaraldehyde in phosphate buffer (0.1 m,p H7 .4). Thes amples for the transmission electron microscopy( TEM)a nd the scanninge lectron microscopy (SEM)o bservations wereprepared according to previously described protocols [43] [44].…”
mentioning
confidence: 99%
“…In case of unfavourable growth conditions, such as starvation or desiccation, these protists can exhibit a resistant form, termed cysts. The cyst structure helps the amoebae to survive various disinfection treatments [1], [2], [3]. Thus, amoebae may bypass all the barriers present in drinking water treatment plants [4] and may reach the water distribution system, where they may colonize biofilms and sediments.…”
Section: Introductionmentioning
confidence: 99%